Hierarchical macroporous polymer structures fabricated by coassembly of polymersomes and polymer brushes - Xianyi Liu; Hanying Zhao (Giant, 2024)
Synthesis of hierarchical macroporous structures has aroused great interest due to the potential applications and unique properties of the materials. In this research, polymersomes and polymer brush-grafted silica particles are used as building blocks for the fabrication of hierarchical macroporous polymer particles. In order to investigate the mechanism of the self-assembly and synthesize hierarchical materials, two-component self-assembly of poly(2-(dimethylamino)ethyl methacrylate)-block-polystyrene (PDMAEMA55-b-PS316) and PS343, and three-component self-assembly of PDMAEMA55-b-PS316, PS343 and PS brushes on silica particles (SiO2-PS343) in THF/methanol mixtures were performed. In the coassembly of PDMAEMA55-b-PS316 and PS343, with an increase in PS343 content the morphology of the self-assembled structures changes from spherical micelles, to polymersomes, and to aggregated polymersomes. In the coassembly of PDMAEMA55-b-PS316, PS343 and SiO2-PS343, aggregated polymersomes and silica particles are formed. After etching silica particles with HF acid, macroporous polymer structures are produced. After quaternization of PDMAEMA blocks with methyl iodide, hierarchical macroporous structures with hydrophilic quaternized PDMAEMA blocks at the coronae and hydrophobic PS domains inside the structures are produced in aqueous solution. Toluene, used as a model compound, is able to diffuse into the hydrophobic domains of the structures, and at high toluene content a transition from the hierarchical macroporous structures to hollow structures is observed.